Influence of Carbon Layer on the Properties of Ni-Based Ohmic Contact to n-Type 4H-SiC. (28th February 2013) - Kuchuk, A.; Kladko, V.; Adamus, Z.; Wzorek, M.; Borysiewicz, M.; Borowicz, P.; Barcz, A.; Golaszewska, K.; Piotrowska, A.
Abstract : Nickel-based contacts with additional interfacial layer of carbon, deposited on n-type 4H-SiC, were annealed at temperatures ranging from 600 to 1000°C and the evolution of the electrical and structural properties were analyzed by I-V measurements, SIMS, TEM, and Raman spectroscopy. Ohmic contact is formed after annealing at 800°C and minimal specific contact resistance of about2 . 0 × 10 - 4 Ω cm 2 has been achieved after annealing at 1000°C. The interfacial carbon is amorphous in as-deposited state and rapidly diffuses and dissolves in nickel forming graphitized carbon. This process activates interfacial reaction between Ni and SiC at lower temperature than usual and causes the formation of ohmic contact at relatively low temperature. However, our results show that the specific contact resistance as well as interface quality of contacts was not improved, if additional layer of carbon is placed between Ni and SiC.